PENGARUH REVITALISASI SUNGAI TERHADAP KINERJA SISTEM DRAINASE KALI PEPE HILIR KOTA SURAKARTA - Reza Eka Putri Damayanti; Kuswanto Nurhadi; Isti Andini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
Flood in Surakarta mostly due to overflowing rivers that flow through the region of Surakarta. The river is part of the urban drainage system. Department of Public Works (DPU) as the local government agency is responsible for the drainage management in Surakarta. One of form of implementation of the river management as part of drainage system is river revitalization program of Pepe River downstream which performed by the DPU. Despite Pepe River downstream revitalization program has been implemented in a variety of activities, the event of flooding due to overflowing Pepe River downstream still occur. Where as the flood is one of the performance indicators of urban drainage system. Thus, from that background it can be defined in research formulation problems, that is how the influence of the river revitalization performed by the DPU Surakarta against Pepe River downstream performance as part of urban drainage system in Surakarta. This research uses quantitative descriptive analysis supported by several analytical techniques including descriptive narrative analysis to identify the characteristics of the revitalization of Pepe River downstream and paired simple t-test analysis to identify the changes of drainage system performance. Next, the relations from the results of both analysis will be identified using explanatory descriptive analysis. Based on the analysis results, it shows that the characteristics of the revitalization of Pepe River downstream is categorized in moderate intensity, because it only includes physical and social activities. Although there are improved changes in the drainage system performance. On the river section I, there are less significant changes with the number of the biggest changes ison the indicator of gabions, that is 11. On the river section II, the drainage system performance changes are significant with the number of the biggest changes is on the indicator of sedimentation, that is 38. In river section III, there are less significant changes with the number of the biggest change is on the indicator of garbage accumulation, with a score of 21.Therefore, it can be argued that the river revitalization program performed by the DPU Surakarta affects the Pepe River downstream performance as the primary drainage channel in the drainage system in Surakarta. The influence can be seen from the reversion of river functions as a drainage channel which is marked by changes in Pepe River downstream drainage system performance from before the river revitalization performed and after the revitalization performed, which is improved. Keywords: river revitalization, catchment area, drainage system performence